Cipières : community and landscape in the Alpes-Maritimes, France - Austin, David, 1947-; Faith, Rosamond, 1935-; Fleming, Andrew; Siddle, David (David J.) (Windgather Press, 2013)
Cipières, in the Alpes-Maritimes, is a French upland landscape rich in archaeology and distinctive in its topography. Cipières: Community and Landscape in the Alpes-Maritimes is a unique exploration which brings together a wealth of documentary sources retained in the village with material evidence in the landscape to produce an interdisciplinary and holistic account of the development of one community and its lands. Beginning with a history of the Project, the volume examines the village's morphology and archaeology, including a landscape survey and investigation of the agrarian systems of the Plâteau de Calern, before moving on to examine settlement patterns, population, politics, social structure and the local economy from the fifth century through to 1900. After a period of decline, the area is now undergoing regeneration, and history is bought up-to-date and placed in its modern context through reflections of the modern day region.